Coaching Clinic in Writing Scientific Articles for High Impact Journals – Part 1 - Agus Purwanto; Khaerul Fahmi; Yoyok Cahyono (Journal of Community Service and Engagement, 2023)
This community service activity aims to provide training on writing scientific articles and publications in reputable international journals for Lecturers at Pramita University Indonesia. The problems faced by several lecturers experi-enced obstacles in publishing reputable international journals, namely lack of insight into the ability to write articles, limited time, busyness, limited language and limited access to journals, availability of online journal subscriptions. The training method is in the form of virtual delivery of material through the zoom application and participants can discuss, ask questions directly without the need to gather. At the end of the activity, a question and answer session was carried out as a form of evaluation. The results after attending the training, the participants managed to compile and publish several articles in reputable national and international journals.